Applied probability for engineers - Suhir, Ephraim ([S.l.] : McGraw-Hill Professional Publishing, 1997)
This text is a concise guide to the principles of probability as used in the design and anlysis of engineered products and systems. With today's demand for total quality, products must be enigneered to have an extended lifetime, operating effectivly at all times to match the user's expectations. This book covers probabilistic methods and approaches used in engineering design and analysis in such disciplines as mechanical, civil, electrical, communications and quality engineering. Its emphasis is on structural analysis and mechanical design as well as practical applications.